Testing and verification in service‐oriented architecture: a survey. (9th May 2012) - Bozkurt, Mustafa; Harman, Mark; Hassoun, Youssef
SUMMARY Service‐oriented architecture (SOA) is gaining momentum as an emerging distributed system architecture for business‐to‐business collaborations. This momentum can be observed in both industry and academic research. SOA presents new challenges and opportunities for testing and verification, leading to an upsurge in research. This paper surveys the previous work undertaken on testing and verification of service‐centric systems, which in total are 177 papers, showing the strengths and weaknesses of current strategies and testing tools and identifying issues for future work. Copyright © 2012 John Wiley & Sons, Ltd.